Spectral techniques : algorithms, analyses and applications - Yan, Shixing (2008)
Spectral techniques which are a mathematical discipline in abstract harmonic analysis have been widely used in many applications including logic design and optimization and digital signal processing. This dissertation is devoted to the developments of the new algorithms, analyses and applications of spectral techniques.